NASH Is the Most Rapidly Growing Etiology for Acute‐on‐Chronic Liver Failure‐Related Hospitalization and Disease Burden in the United States: A Population‐Based Study. Issue 5 (17th April 2019) - Axley, Page; Ahmed, Zunirah; Arora, Sumant; Haas, Allen; Kuo, Yong‐Fang; Kamath, Patrick S.; Singal, Ashwani K.
Abstract : Acute‐on‐chronic liver failure (ACLF) is characterized by multiple organ failure (OF) with high short‐term mortality. There is lack of population‐based data on trends on etiology specific ACLF related burden. National Inpatient Sample (2006‐2014) was queried using ICD‐09 codes for admissions with cirrhosis and ACLF (≥2 extrahepatic OF). Of 1, 928, 764 admissions for cirrhosis between 2006 and 2014, 112, 174 (5.9%) had ACLF (4.5%, 1.2%, and 0.2% with ACLF 1, 2, and 3, respectively). The brain was the most common OF in 11.9%, followed by respiratory failure in 7.7%, cardiac failure in 6.3%, and renal failure in 5.6%. ACLF increased by 24% between 2006 and 2014 with a 63% increase in 179, 104 patients with nonalcoholic steatohepatitis (NASH) cirrhosis (3.5% to 5.7%); a 28% increase in patients with 429, 306 alcoholic cirrhosis (5.6% to 7.2%); a 25% increase in patients with 1, 091, 053 with other etiologies (5.2% to 6.5%); and no significant change in 229, 301 patients with viral hepatitis (VH) (4.0% to 4.1%). In‐hospital mortality was higher among ACLF patients compared with patients without ACLF (44% versus 4.7%; P <  0.0001). Each NASH‐related ACLF patient compared with other etiologies had a longer mean length of stay (14 versus 12 days), was associated with higher median total charges (US $151, 196 versus US $134, 597), and had more frequent use of dialysis (45% versus 36%) and longterm care (32% versus 26%; P  < 0.0001 for all). Results remained similar in a subgroup analysis after including half of admissions with cryptogenic cirrhosis as NASH. In conclusion, NASH cirrhosis is the most rapidly growing indication for ACLF‐related hospitalization and use of hospital resources. In the setting of improved treatment options for chronic hepatitis, the health care burden of chronic viral‐related liver disease remains stable. Population‐based strategies are needed to reduce the health care burden of cirrhosis, particularly related to NASH.